Problems and Prospects of Using «Green» Finance by Territorial Communities: world Experience and Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Scientific novelty of the article is that it is revealed in it theoretical and practical features of the using of «green» financial form stimulation that the territorial communities can use in the development «green» economy in Ukraine, because forms are used to achieve ecological tasks set for our country in international environmental agreements, so far do not give proper results.It complicates the receipt of foreign environmental investments not only at the state level, but also at the local level. The present study analyzes the experience of developed countries on this issue and outlines ways of its using in Ukraine, primarily at the level of united territorial communities.It is substantiated that they should become a test ground for implementing promising forms of «green» finance in our country, but for this purpose it is important for the  united territorial communities to develop the appropriate system of incentive and state’s insurance in case of failure in the implementation of environmental projects. Little attention is given to this issue, since in the foreground the state’s «green»financial incentives. Differentiated concepts such as «green» finance and climatic finance, which is often identified in financial science.The content of financial and economic regulation in the field is specified nature management, because quite often this concept is considered as the only one the whole, which complicates the use of «green» finance at different levels management.The practical significance of the article is to substantiate the necessity of more active using of such mechanisms of «green» financing as local «green» bonds, «green» credit of communal banks, «revolver» funds, «green» tariffs, «warm» credit, etc. which will bring the practice  of nature management in Ukraine to EU norms and international environmental requirements organizations. The article reveals the problems of application of separate forms of «green» local finance and ways to overcome them with consideration the experience of the leading countries of the world.
Keywords: «green» finance, united territorial communities, municipal-private partnership, «green» foreign investments,environmental taxes, EU, Ukraine